Esports Associations and the Pursuit of Legitimacy: Evidence From Germany - Heidenreich, Heiko; Brandt, Christian; Dickson, Geoff; Kurscheidt, Markus (Frontiers in Sports and Active Living, 2022)
The dominant position of esports game publishers is a fundamental difference between the systemic governance of esports and traditional sports. There are no such equivalent organizations in traditional sports. As for-profit corporations, the publishers develop and market the electronic games as their commercial products and, thus, possess exclusive property rights. Publishers control the virtual sporting environment and the rules of the game. In conventional sports, by contrast, non-profit associations administer their sports with the core task of developing the sport by regulations, playing rules, and licensing. There are, however, esports associations which resemble traditional leagues and national governing bodies. Given this, we explore how esports associations pursue legitimacy. This study is empirically motivated by the recent emergence of two esports associations in the insightful case of Germany and examines the pursuit of legitimacy by the World Esports Association (WESA) and the eSport-Bund Deutschland e.V. (ESBD). The study is based on a content analysis of 55 documents and nine interviews with relevant stakeholders. The findings show that the esports associations rely on conformance and manipulation strategies by transferring existing structures from traditional sports to esports. The most effective practices are lobbying for social and public acceptance of esports and creating supportive networks for esports development. While publishers possess an undisputed and taken-for-granted legitimacy based on their product property rights, esports associations struggle for recognition and acceptance. They may still have a long way to go, given that established associations in conventional sports have a history for decades. Yet, esports associations need to accept publisher dominance. Thus, they can only claim partial legitimacy within the esports ecosystem by targeting segments of stakeholders. Management, policy and theoretical implications of this key insight are finally presented.